Chinese patent herbal medicine (Shufeng Jiedu capsule) for acute upper respiratory tract infections: A systematic review and meta-analysis - Zhang, Ying-ying (Integr Med Res, 2021)
Background: Shufeng Jiedu capsule has been widely used in China for acute upper respiratory tract infections (AURTIs). The aim of this study was to evaluate its effectiveness and safety for AURTIs. Methods: Randomized controlled trials comparing SFJD with conventional drug for patients with AURTIs were included. Eight databases were searched from their inceptions to February 2021. Data was synthesized using risk ration (RR) or mean difference (MD) with their 95% confidence interval (CI). The primary outcome was resolution time of typical symptoms. Results: Twenty-five RCTs involving 3410 patients were included. SFJD in combination with conventional drug was associated with; in common cold shortening the duration of fever (MD −1.54 days, 95% CI [−2.15,−0.92], I(2) = 80%, n = 385, 3 trials) and cough (MD −1.22 days, 95% CI [−1.52, −0.93]); in herpangina, shortening the duration of fever (MD -0.68 days, 95% CI [−1.15, −0.21], I(2) = 68%, n = 140, 2 trials) and blistering (MD −0.99 days, 95% CI [−1.23, −0.76], n = 386, 3 trials); in acute tonsillitis and acute pharyngitis shortening the duration of fever (MD −1.13 days, 95% CI [−1.36, −0.90], I(2) = 33%, n = 688, 7 trials) and sore throat (MD −1.13 days, 95% CI [−1.40, −0.86], I(2) = 84.1%, n = 1194, 10 trials). SFJD also improving their cure rate with a range (1–5 days). No serious adverse events were reported. Conclusion: Low certainty evidence suggests that SFJD appears to shorten the duration of symptoms in AURTIs, improve cure rate and seems safe for application. However, high quality placebo controlled trials are warranted to confirm its benefit.